Carob (Ceratonia siliqua L.) flour as a functional ingredient in fresh wheat pasta: Effect on its technological and sensory properties, oral processing and in vitro health benefits - Susana Ribes; Héctor Gómez-Llorente; Laura Córdoba; Isabel Fernández-Segovia; Ana Albors; José M. Barat; Édgar Pérez-Esteve (Food Research International, 2025)

Nutrients on the move: Investigating large scale fatty acid exports from European ponds via emerging insects - Lena Fehlinger; Fernando Chaguaceda; Pietro Tirozzi; Marina Tomás‐Martín; Ellinor Jakobsson; Teofana Chonova; Benjamin Misteli; Alberto Scotti; Jorge F. Henriques; Juan Rubio‐Ríos; Daniel Morant; Pierre Marle; et al. (Limnology and Oceanography, 2025)
Permanent ponds are key landscape units that supply various ecosystem services. Notably, the export of aquatic subsidies to land via emerging insects may significantly influence terrestrial food webs. Polyunsaturated fatty acids (PUFA), which enhance consumer fitness, are among the essential exported components. The patterns and drivers of dietary exports from ponds via insects remain poorly known, particularly at continental scales. We analyzed the exports of biomass, lipid, and fatty acid contents from emerging insects, sampled in 36 ponds across 11 European countries, from 36°N to 59°N and from 26°W to 19°E, over four seasons. We found that biomass and fatty acid exports decreased with increasing latitude and were higher in spring and summer. Seasonal effects also increased with higher latitudes. Temperature was the most important predictor of insect biomass, explaining 27.6% of the total variation and showing an unimodal response. Thus, increasing temperature may promote exports in colder regions and seasons but may negatively influence biomass exports in already warm regions. The exports of total lipids, PUFA, and eicosapentaenoic acid were correlated to exported biomass, while those of docosahexaenoic acid were linked to the emergence of Chaoboridae. Our findings indicated that PUFA contents were affected by taxonomic insect community composition and pond trophic state (indicated by chlorophyll a ). Two of the correlates identified here (temperature and trophic state) are influenced by anthropogenic activity via climate and land use change, respectively. Thus, human activity impacts the food webs in and around ponds by influencing the quantity and quality of nutritional exports.

Temporal evolution of the performance evaluation of the laboratories at Spanish nuclear power plants in water samples - José Antonio Suárez-Navarro; Virginia Peyres; Ana Isabel Sánchez-Cabezudo; Nuria Navarro; Victor Manuel Expósito-Suárez; Jordi Español; José Manuel Arteaga; Manuel Brun; Rosaura Miret; Ana Llorente; Mercedes Ibañez; J. F. Benavente (Environmental Monitoring and Assessment, 2025)
This study examined the performance evaluation and analysis of the laboratories of Spanish Nuclear Power Plants over the last 9 years of the 34 editions organized by CIEMAT. The participating nuclear power plants were Almaraz, Ascó I, Ascó II, Cofrentes, Santa María de Garoña, Trillo, and Vandellós II. The radionuclides analyzed were those necessary to ensure operational radiological protection and the control of liquid effluents from a nuclear power plant. The radionuclides are classified into beta emitters: 3 H, 14 C, and 90 Sr, and gamma emitters: 241 Am, 57 Co, 137 Cs, and 60 Co. The results of the z score showed that the performance in determining 3 H was 100% satisfactory in most years, except in 2010 and 2014, where percentages of 83% and 87.5% were recorded, respectively. 90 Sr showed greater variability with a satisfaction range between 60 and 100%. Furthermore, the gamma emitters achieved satisfactory evaluations above 93% within the studied time range. The analysis of the distributions of the relative differences between the laboratory results and the reference values confirmed that the distributions were normal according to the Shapiro–Wilk test, with a percentage of outlier values below 5%. Additionally, linear regression analysis was used to evaluate the dispersion of the results relative to the reference values through the RSE parameter, being highest for 3 H and 14 C. The PomPlot graphs allowed for the visualization of the relationship between the obtained results and the reference values, indicating that, although high percentages of satisfactory evaluations were achieved, certain trends in the laboratory results must be considered to detect potential future deviations in the analytical methodologies.

Non-thermal inactivation of Alicyclobacillus acidoterrestris and guaiacol production in orange juice by using silica microparticles functionalised with essential oil components - Héctor Gómez-Llorente; Oumaima Moumane; Sergio Grau-Martínez; Ana Isabel Jiménez-Belenguer; Manuel Hernández; María Ruiz-Rico; José M. Barat; Isabel Fernández-Segovia; Édgar Pérez-Esteve (Food Control, 2025)

Azospirillum brasilense and Azospirillum argentinense inoculation and salt stress modify antioxidant enzymes profile during in vitro rooting of jojoba - Ana J. Gonzalez; Mauro E. Yarte; Berta E. Llorente; Ezequiel E. Larraburu (South African Journal of Botany, 2024)

Island biodiversity in peril: Anticipating a loss of mammals' functional diversity with future species extinctions - Sonia Llorente‐Culebras; Carlos P. Carmona; William D. Carvalho; André Menegotto; Rafael Molina‐Venegas; Richard J. Ladle; Ana M. C. Santos (Global Change Biology, 2024)
Islands are biodiversity hotspots that host unique assemblages. However, a substantial proportion of island species are threatened and their long‐term survival is uncertain. Identifying and preserving vulnerable species has become a priority, but it is also essential to combine this information with other facets of biodiversity like functional diversity, to understand how future extinctions might affect ecosystem stability and functioning. Focusing on mammals, we (i) assessed how much functional space would be lost if threatened species go extinct, (ii) determined the minimum number of extinctions that would cause a significant functional loss, (iii) identified the characteristics (e.g., biotic, climatic, geographic, or orographic) of the islands most vulnerable to future changes in the functional space, and (iv) quantified how much of that potential functional loss would be offset by introduced species. Using trait information for 1474 mammal species occurring in 318 islands worldwide, we built trait probability density functions to quantify changes in functional richness and functional redundancy in each island if the mammals categorized by IUCN as threatened disappeared. We found that the extinction of threatened mammals would reduce the functional space in 63% of the assessed islands, although these extinctions in general would cause a reduction of less than 15% of their overall functional space. Also, on most islands, the extinction of just a few species would be sufficient to cause a significant loss of functional diversity. The potential functional loss would be higher on small, isolated, and/or species‐rich islands, and, in general, the functional space lost would not be offset by introduced species. Our results show that the preservation of native species and their ecological roles remains crucial for maintaining the current functioning of island ecosystems. Therefore, conservation measures considering functional diversity are imperative to safeguard the unique functional roles of threatened mammal species on islands.

Machine learning screening tools for the prediction of extraction yields of pharmaceutical compounds from wastewaters - Ana Casas; Diego Rodríguez-Llorente; Guillermo Rodríguez-Llorente; Juan García; Marcos Larriba (Journal of Water Process Engineering, 2024)

Neuroscience tools to study the effect of the presentation form on food-evoked emotion for senior population - Ana B. Baranda; Yolanda Ríos; Raquel Llorente; Ana Belén Naranjo; Noelia da Quinta (Food Research International, 2024)

Biochemical changes by Azospirillum brasilense enhance jojoba rooting under salt stress - Ana J. Gonzalez; Mauro E. Yarte; Berta E. Llorente; Ezequiel E. Larraburu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Plant growth promoting bacteria mitigates salt stress during Handroanthus impetiginosus in vitro rooting - Mauro Enrique Yarte; Ana Julia González; Berta Elizabet Llorente; Ezequiel Enrique Larraburu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Publication trends in global biodiversity research on protected areas - Sonia Llorente-Culebras; Richard J. Ladle; Ana M.C. Santos (Biological Conservation, 2023)

Novel clinical and immunological features associated with persistent post-acute sequelae of COVID-19 after six months of follow-up: a pilot study - Jiram Torres-Ruiz; Julieta Lomelín-Gascón; Jaquelin Lira Luna; Ana Sofia Vargas- Castro; Alfredo Pérez-Fragoso; Miroslava Nuñez-Aguirre; Beatriz Alcalá-Carmona; Abdiel Absalón-Aguilar; Jennifer T. Balderas-Miranda; José Luis Maravillas-Montero; Nancy R. Mejía-Domínguez; Carlos Núñez-Álvarez; et al. (Infectious Diseases, 2023)

Polyphasic identification and MAT1-2 isolates of Phyllosticta citricarpa in Cuba - Wendy Serra; María B. Lugo Álvarez; Dariel García Rodríguez; Eugenio Alonso-Oliva; Amalia Sanz Llorente; Vladimiro Guarnaccia; Elma Carstens; Jeffrey A. Rollins; Sofie Thijs; Jaco Vangronsveld; Ana M. Manzano León (European Journal of Plant Pathology, 2022)

Azospirillum brasilense mitigates anatomical alterations produced by salt stress in jojoba in vitro plants - Ana Julia Gonzalez; Ezequiel Enrique Larraburu; Berta Elizabet Llorente (Vegetos, 2021)

The decline of mussel aquaculture in the European Union: causes, economic impacts and opportunities - Lamprakis Avdelas; Edo Avdic‐Mravlje; Ana Cristina Borges Marques; Suzana Cano; Jacob J. Capelle; Natacha Carvalho; Maria Cozzolino; John Dennis; Tim Ellis; José M. Fernández Polanco; Jordi Guillen; Tobias Lasner; et al. (Reviews in Aquaculture, 2021)
In contrast to the increasing aquaculture production of mussels worldwide, production in the European Union (EU) has shown a decreasing trend over the last two decades. Aquaculture production of mussels in the EU peaked in the late 1990s at more than 600 000 tonnes; by 2016, production volume had dropped by 20% to 480 000 tonnes. As mussel production represents more than ⅓ of EU aquaculture production, this decrease is an important contributor to the stagnation of EU aquaculture. Previous studies have suggested diseases, lack of mussel seed (spat), and low profitability as the main causes of the EU mussel production decrease. In this study, we investigate how economic and environmental factors have contributed. Moreover, we examine if the different mussel production techniques (raft, longline, on‐bottom, and ‘bouchot’) have been differently affected, by analysing the economic performance and cost structure evolution for the period 2010–2016. We complement these results with a SWOT (strengths, weaknesses, opportunities, and threats) analysis of the EU mussel sector based on expert knowledge.

High overlap between traditional ecological knowledge and forest conservation found in the Bolivian Amazon - Jaime Paneque-Gálvez; Irene Pérez-Llorente; Ana Catarina Luz; Maximilien Guèze; Jean-François Mas; Manuel J. Macía; Martí Orta-Martínez; Victoria Reyes-García (Ambio, 2018)

2-AG promotes the expression of conditioned fear via cannabinoid receptor type 1 on GABAergic neurons - Alvaro Llorente-Berzal; Ana Luisa B. Terzian; Vincenzo di Marzo; Vincenzo Micale; Maria Paz Viveros; Carsten T. Wotjak (Psychopharmacology, 2015)

Clinical infection of Cantabrian chamois (Rupicapra pyrenaica parva) by louping ill virus: new concern for mountain ungulate conservation? - Francisco Ruiz-Fons; Ana Balseiro; Kim Willoughby; Álvaro Oleaga; Mark P. Dagleish; Elisa Pérez-Ramírez; Sabina Havlíková; Boris Klempa; Francisco Llorente; María Paz Martín-Hernando (European Journal of Wildlife Research, 2014)

From Steam to Diesel in the Spanish Fisheries Sector: A Multilevel Perspective in the Study of Technology Diffusion Processes - Ana I. Sinde-Cantorna; G. Álvarez-Llorente; I. Diéguez-Castrillón (Coastal Management, 2013)